A comparative analysis of the education systems in Brunei Darussalam and Indonesia: Curriculum, Islamic education, and character development - Dinna Nurul Izza Arofah; Mahmud Arif; Hajah Rafidah binti Haji Abdullah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2026)
Purpose - This study aims to comparatively analyze the education systems of Brunei Darussalam and Indonesia by examining educational governance, curriculum reform, Islamic education, and character development within the context of Muslim-majority countries. Design/methods/approach - This study employed a qualitative library research design using a comparative document analysis approach. Data were collected from 27 documentary sources, including academic books, peer-reviewed journal articles, government regulations, curriculum documents, and official institutional publications. The data were analyzed through qualitative content analysis involving document selection, thematic coding, cross-country comparison, and interpretative analysis. Findings - The findings reveal that Brunei Darussalam adopts a centralized education system in which educational governance, SPN21, Islamic education, and character development are systematically integrated through the philosophy of Melayu Islam Beraja (MIB). In contrast, Indonesia implements a decentralized education system that promotes institutional diversity through the Merdeka Curriculum, multiple pathways of Islamic education, and the Pancasila Student Profile. Although the two countries employ different governance and curriculum models, both successfully integrate Islamic values with twenty-first-century competencies to develop academically competent, morally responsible, and religiously grounded graduates. Research implication/limitation - The findings highlight that educational governance significantly influences curriculum implementation, the institutional integration of Islamic education, and character development. The study provides comparative insights that may inform educational reform and policy development in Muslim-majority countries. Originality/value - This study offers an integrated comparative perspective by demonstrating how educational governance shapes curriculum reform, Islamic education, and character development in two Muslim-majority education systems.